EFEKTIFITAS PROGRAM EDUKASI DALAM MENINGKATKAN KEPATUHAN MINUM OBAT PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS MACCINI SAWAH - Nur Adha Salsabila Patuti; Andi Mappanganro; Tutik Agustini; Akbar Asfar (Jurnal Kesehatan, 2026)
Hypertension is a chronic disease with a low rate of medication adherence. Many patients only take medication when symptoms occur, which increases the risk of complications. Health education plays an important role in improving patients’ understanding and behavior related to hypertension therapy. Objective: To determine the effectiveness of an education program in improving medication adherence among hypertension patients. Methods: This study employed a pre-experimental design with a pretest-posttest approach. Data were collected through observation sheets and interviews. Results: Before receiving education, the patient only took medication when experiencing symptoms, with a blood pressure of 165/95 mmHg. After the educational intervention, the patient demonstrated improved knowledge, started using a phone alarm as a reminder, and showed better medication adherence. Blood pressure decreased to 150/90 mmHg. Conclusion: The education program was proven effective in improving patients’ knowledge and adherence to antihypertensive medication. Continuous education that is simple, easy to understand, and involves family support plays a crucial role in controlling blood pressure and preventing long-term complications.